Pandemics, intellectual property and ‘our economy’: A worldview analysis of Canada’s role in compromising global access to COVID-19 vaccines - Ben Brisbois; Katrina Plamondon; David Walugembe; Rodrigo Curty Pereira; Christine Edet; Jenna Dixon; Roojin Habibi; Mohammad Karamouzian; Ronald Labonté; Srinivas Murthy; Vardit Ravitsky (Global Public Health)
Despite self-congratulatory rhetoric, Canada compromised COVID-19 vaccine equity with policies impeding a proposed global waiver of vaccine intellectual property (IP) rules. To learn from Canada’s vaccine nationalism we explore the worldview – a coherent textual picture of the world – in a sample of Government of Canada communications regarding global COVID-19 vaccine sharing. Analysed documents portray risks and disparities as unrelated to the dynamics and power relations of the Canadian and international economies. Against this depoliticised backdrop, economic growth fueled by strict IP rules and free trade is advanced as the solution to inequities. Global vaccine access and distribution are pursued via a charity-focused public-private-partnership approach, with proposals to relax international IP rules dismissed as unhelpful. Rather than a puzzling lapse by a good faith ‘middle power’, Canada’s obstruction of global COVID-19 vaccine equity is a logical and deliberate extension of dominant neoliberal economic policy models. Health sector challenges to such models must prioritise equity in global pandemic governance via politically assertive and less conciliatory stances towards national governments and multilateral organisations. Mobilisation for health equity should transform the overall health-damaging macroeconomic model, complementing efforts based on specific individual health determinants or medical technologies.